2020
DOI: 10.1111/brv.12625
|View full text |Cite
|
Sign up to set email alerts
|

When one tail isn't enough: abnormal caudal regeneration in lepidosaurs and its potential ecological impacts

Abstract: Abnormal caudal regeneration, the production of additional tails through regeneration events, occurs in lepidosaurs as a result of incomplete autotomy or sufficient caudal wound. Despite being widely known to occur, documented events generally are limited to opportunistic single observations – hindering the understanding of the ecological importance of caudal regeneration. Here we compiled and reviewed a robust global database of both peer‐reviewed and non‐peer reviewed records of abnormal regeneration events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 99 publications
3
30
0
Order By: Relevance
“…Here we observed another case for a Tropidurus species, likely due to the widespread distribution and high abundance of this species in Northeastern Brazil, as well as its frequent occurrence in anthropized environments. Although this phenomenon is common in nature, it likely does not affect the survival and reproductive success of individuals, as has been reported in the literature (Martins et al 2013, Passos et al 2014, Barr et al 2020) and our observation, as in one of our reports, the individual was in the process of mating.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Here we observed another case for a Tropidurus species, likely due to the widespread distribution and high abundance of this species in Northeastern Brazil, as well as its frequent occurrence in anthropized environments. Although this phenomenon is common in nature, it likely does not affect the survival and reproductive success of individuals, as has been reported in the literature (Martins et al 2013, Passos et al 2014, Barr et al 2020) and our observation, as in one of our reports, the individual was in the process of mating.…”
supporting
confidence: 85%
“…In addition, it may be related to adverse environmental conditions caused by pollutants or pathogens that cause these malformations (Martinelli & Bogan 2013). Some records of bifurcated tails have been highlighted in the available literature on the lizard species Tropidurus torquatus (Martins et al 2013 28 (Andrade et al 2015) Ameiva ameiva (Gogliath et al 2012), Salvator merianae (Pelegrin & Leão 2016), Ameivula ocellifera (Sales & Freire 2019), and Iguana iguana (Lozano & Siro 2020), lepidosaurs (Barr et al 2020). Here we observed another case for a Tropidurus species, likely due to the widespread distribution and high abundance of this species in Northeastern Brazil, as well as its frequent occurrence in anthropized environments.…”
mentioning
confidence: 99%
“…A tail bifurcation on the regenerate often indicates that the tail can be broken in this part. However, recent research has shown that bifurcation can occur in non-autotomic species [36] too. They demonstrate that an abnormal regeneration can occur in lizards with intra-vertebral autotomy, inter-vertebral autotomy and in some species that have lost the ability to autotomy.…”
Section: Resultsmentioning
confidence: 99%
“…Caudal autotomy is a major defense mechanism in 13 lizard families (Downes and Shine 2001). Abnormal tail regenera-tion (from bifurcations to hexafurcations) is the result of previous injury rather than developmental tail deformity (Lynn 1950) and also has been reported in several lizard families (Barr et al 2020). Tail bifurcation in a Tokay Gecko was recorded by Gogoi et al (2018) in Kaziranga, Assam, India; however, this observation is the first record from Nepal.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 96%